Studying the Iroteolytic Activity of the Mushroom Aspergillus Oryzae - D., Mirzayeva; Sh., Komilova (American Journal of Biomedicine and Pharmacy, 2025)
The article is devoted to proteases, which are industrially important enzymes and are successfully used in the food, pharmaceutical and many industries. And pepsin is an enzyme of animal origin, characterized by a number of properties, but the production of which is dependent on the supply of animal rennet. The study of microbial producers, the resulting proteases like pepsin, is a very relevant and highly effective area both in enzymology and in practical terms.